2018
DOI: 10.3201/eid2408.171595
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Surveillance for Coccidioidomycosis, 14 US States, 2016

Abstract: Although coccidioidomycosis in Arizona and California has been well-characterized, much remains unknown about its epidemiology in states where it is not highly endemic. We conducted enhanced surveillance in 14 such states in 2016 by identifying cases according to the Council of State and Territorial Epidemiologists case definition and interviewing patients about their demographic characteristics, clinical features, and exposures. Among 186 patients, median time from seeking healthcare to diagnosis was 38 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 17 publications
4
44
0
Order By: Relevance
“…Although the CDC designates coccidioidomycosis as a reportable disease, reporting is dependent upon the participation of individual state departments of health. A recent report documented delays of up to four and a half years in accurately diagnosing patients with coccidioidomycosis who presented in states not known to be endemic for this disease [2]. It is possible that if Texas participated in the reporting of this disease, this child's infection might have been identified in a more timely manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CDC designates coccidioidomycosis as a reportable disease, reporting is dependent upon the participation of individual state departments of health. A recent report documented delays of up to four and a half years in accurately diagnosing patients with coccidioidomycosis who presented in states not known to be endemic for this disease [2]. It is possible that if Texas participated in the reporting of this disease, this child's infection might have been identified in a more timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, most reported infections originate from exposures in Arizona and California, but unexpected infection sources are continuing to be found elsewhere in the western USA [1]. Infections are also recognized outside of known endemic areas [2], usually associated with recent travel to and exposure in known endemic regions. Less frequently, they are reactivation during immunosuppression from a distant past infection or from transplantation of infected tissue.…”
Section: Introductionmentioning
confidence: 99%
“…C. immitis is primarily found in the Central Valley of California but has now been found as far north as eastern Washington state [ 119 , 129 134 ]. C. posadasii, is found in the desert areas of Arizona, Texas, Utah, Mexico, and Central and South America [ 6 , 133 , 135 140 ]. However, there is geographic overlap between the two species in Southern California [ 122 ].…”
Section: Methodsmentioning
confidence: 99%
“…Turabelidze et al reported a fivefold increase in the incidence of cases in Missouri from 0.05 per 100,000 population in 2004 to 0.28 per 100,000 in 2013, with about a quarter of the cases either having no reported travel to the known endemic areas or no travel history [ 139 , 153 ]. Meanwhile, a surveillance study in 14 states by Benedict et al in 2016 identified Utah, Nevada, and New Mexico as low endemic areas compared to 11 other states including Missouri that were deemed non-endemic [ 135 ]. The study also highlighted the need for increased awareness of coccidioidomycoses in areas of low endemicity to avoid delay in its accurate diagnosis [ 135 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation